The essential guide to freelance writing how to write, work, & thrive on your own terms - Petit, Zachary (Writer's Digest Books, 2015)
"So you want to be a freelance writer. Great! But now you're faced with a laundry list of questions: Should I freelance full time or part time? Should I write for magazines, newspapers, or online markets? How do I dream up the perfect article idea, and how do I pitch it successfully? How do I negotiate contracts, foster relationships with editors, and start getting steady work while avoiding financial panic attacks and unpleasant ulcers? The Essential Guide to Freelance Writing won't just show you how to survive your freelancing writing career--it will teach you how to truly thrive" -- provided by publisher.